Membangun personal branding lewat keahlian desain grafis dan publikasi sebagai persiapan memasuki Dunia Usaha dan Dunia Industri (DUDI) - Al Zuhri; Fathayatul Husna; Ulfa Khairina; Ibnu Phonna Nurdin; Anhar Fazri; Jilantahani Jilantahani; Desi Fauziah; Halil Mulya (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2026)
Graphic design and publication are important competencies students need in the digital era, especially for creating promotional media and self-branding. SMAN 2 Meulaboh has adequate facilities to support this, but they have not been optimized. The lack of competent teaching staff in graphic design and publication is a major obstacle. As an effort to overcome this problem, we from the Communication Science Study Program at Teuku Umar University provided graphic design and publication services, including banner design, using Adobe Photoshop. Socialization, demonstration, discussion, testing, competition, and appreciation were employed as methods in this program, following the Planning, Implementing, and Evaluating (PIE) stages, involving 15 students from class XI at SMAN 2 Meulaboh. The pre-test results showed that only 17% (3 out of 15) of students knew about graphic design and publication. However, after the service was carried out, the team rechecked the post-test, and the results showed that 87% (13 out of 15) students knew about graphics and publication and could even apply their knowledge directly. This shows that the community service carried out increased students' knowledge, skills, art, and interest in graphic design and publication, especially in the use of Adobe Photoshop for creating banners. Furthermore, it is hoped that this service can be carried out continuously and periodically to achieve maximum results.